Human factor training as a learning intervention for Technical Personnel performance - Rahmat Rahmat; Bambang Heriyadi; M. Giatman; Syahril Syahril (Global Econedu, 2026)
This study aimed to analyze the partial and simultaneous effects of Human Factor Training, Engineer Competence, and Work Motivation on Aircraft Engineer Performance in the Line Maintenance Unit of Garuda Maintenance Facility AeroAsia. A quantitative descriptive-correlational design was employed. The population consisted of 103 aircraft engineers across three maintenance stations (KNO, CGK, and SUB). Following instrument validation with 30 engineers, 73 engineers were selected as the main sample using cluster random sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 25. Human Factor Training significantly influenced engineer performance (t = 6.642; p < 0.001), as did Engineer Competence (t = 2.192; p = 0.032). In contrast, Work Motivation showed no significant effect (t = 1.763; p = 0.082). Simultaneously, the three variables significantly affected engineer performance (F = 288.248; p < 0.001). Human Factor Training emerged as the strongest predictor of engineer performance, followed by Engineer Competence. Although Work Motivation was positively related to performance, its contribution was not statistically significant, suggesting that performance in aircraft maintenance is more strongly influenced by technical competence, safety training, and compliance with aviation regulations and standard operating procedures.